The effect of fentanyl combined with linezolid on in-hospital mortality in mechanically ventilated patients: A retrospective cohort study - Jia-Hui Niu; Xiao-Jiao Cui; Min Chen; Jin-Qi Li; Xiao-Qing Yi (PLoS ONE, 2026)
Background The combination of linezolid and opioid drugs such as fentanyl may increase the risk of serotonin syndrome, but its impact on in-hospital mortality is not yet clear. The aim of this study is to investigate the effect of simultaneous use of fentanyl and linezolid on in-hospital mortality in mechanically ventilated patients. Method Based on the MIMIC-IV database, 3339 patients receiving mechanical ventilation were enrolled and divided into three groups: the group receiving linezolid simultaneously (n = 43), the group receiving linezolid within 14 days (n = 22) and the group that did not use linezolid (n = 3274). Use multivariate Cox regression analysis to analyze in-hospital mortality rates and adjust for confounding factors. Result The in-hospital mortality rate of the group receiving linezolid simultaneously was 37.2% (16/43), the group receiving linezolid within 14 days was 40.9% (9/22), and the group that did not use linezolid was 22.9% (751/3274). The in-hospital mortality rate of the group receiving linezolid simultaneously was significantly higher than that of the group that did not use linezolid (hazard ratio [HR], 1.56; 95% CI, 1 ~ 2.43; P = 0.049). There was no statistically significant difference in in-hospital mortality rate among the group receiving linezolid within 14 days and the group that did not use linezolid (hazard ratio [HR], 1.01; 95% CI, 0.5 ~ 2.05; P = 0.968). Subgroup analysis showed that there was no interaction between different groups at baseline (age, gender, race, BMI, liver disease, and kidney disease) (interaction p-value > 0.05). Conclusion In this post-hoc analysis, we found an association between the combined use of fentanyl and linezolid and increased in-hospital mortality among mechanically ventilated patients. However, this finding is based on studies with small sample sizes and requires further validation through larger, multicenter investigations. In clinical practice, the potential risks of this drug interaction should be carefully evaluated.